Effect of celery leaves extract on the growth of Candida albicans in patients wearing removable orthodontic appliances - Donald R. Nahusona; Felisia Yovita Thahir (Makassar Dental Journal, 2020)
Background: Maintaining the cleanliness of removable orthodontic appliances is often overlooked so it can lead to changes in Candida albicans into the pathogenic form. Celery leaves are one of the natural ingredients that have active compounds as antimicrobial. Objective: To determine the effects of celery leaf extract in inhibiting the growth of C.albicans found on re-movable orthodontic appliances. Methods: Laboratory experimental studies were conducted with post test only control group design involving 5 samples of removable orthodontic appliances, which were swabbed to obtain C.albicans. Samples were divided into 5 groups, 1 control group and 4 treatment groups with 10%, 30%, 50%, and 70% extract concentration and the inhibitory test was performed. Result: The greater the concentration of celery leaf extract, the greater the diameter of the inhibi-tory zone formed. Conclusion: Celery leaf extract has the effect in inhibiting the growth of C.albicans found on removable or-thodontic appliances.